Heidegger and the possibility of a political field in the age of technology - Pinto Benavides, Héctor (Resonancias. Revista de Filosofía, 2016)
Martin Heidegger is, without a doubt, one of the contemporary philosophers who have more profusely meditated on the matter of the technique. For him, our time is under the unconditioned domain of the essence of modern technique (enframing: das Ge-stell) transforming the human being into a mere abstract entity devoid of any particularity and putting all possible rooting trait in question. In that direction, in the posthumous interview on the german newspaper Die Spiegel (1976), Heidegger states that he is not entirely convinced that democracy is the most appropriate political system for the current age of technique. In light of the developments described above, the present essay attempts to envision a horizon from which to set up a slot for action and production towards a political field in an era dominated by the essence of the technique and the full completion of the metaphysical project of modernity.